Implementation of Public Service Agency for Good University Governance - Selvi, Selvi; Kango, Umin (Asia Pacific Journal of Management and Education (APJME), 2020)
This study aims to analyze the extent to which the implementation of the concept of Public Service Agency at Gorontalo State University to realize its Good University Governance, and to determine the policy/model/framework of its management under the agency mandate. This study population is the heads in the work units of Gorontalo State University, such as vice chancellors, deans, vice deans, heads of institutions, heads of main offices, and several lecturers and or employees. This study used all populations as the samples and the descriptive statistical approach for its data analysis. The findings contended that all stakeholders of State University of Gorontalo generally understood the implementation of Public Service Agency for Good University Governance.